HERMENEUTIKA AL-QUR’AN MUHAMMED ARKOUN - Ishak Hariyanto (UIN Mataram, 2018)
This paper wants to describe the hermeneutical method of Muhammed Arkoun towards the Qur’an. In Arkoun’s view, the Qur’an needs to be reinterpreted, because when the Qur’an was revealed by Allah it has been in?uenced by the historical and social realities of Arab culture. In addition, Arkoun said that the Qur’an is the incarnation of God’s words conveyed to humans, constructed in human language, transmitted orally by human voices, and written in written form. To reinterpret the Al-Qur’an, a hermeneutical method is needed, namely seeing the hermeneutical circle between text, author, and reader. The text of the Qur’an according to Arkoun is very rich in symbols, meanings, and is always open to all interpretations for readers. So Arkoun views the text of the Qur’an as a free interpretation. A text that remains open and not limited to, interpretation, because an interpretation that can enrich the meaning of a text, so that a text is not only limited to the past but also has an openness to the future so that it can understand the wishes of the author. From that reason, interpreting a text is a task that is never completed. Every age must seek its own interpretation. In this context, the Qur’an is also very freely interpreted according to the times and conditions to give enlightenment to humans with the demands of the times